Current and future targeted alpha particle therapies for osteosarcoma: Radium-223, actinium-225, and thorium-227 - Anderson, Peter M.; Subbiah, Vivek; Trucco, Matteo M. (Frontiers in Medicine, 2022)
Osteosarcoma is a high-grade sarcoma characterized by osteoid formation, nearly universal expression of IGF1R and with a subset expressing HER-2. These qualities provide opportunities for use of the alpha particle-emitting isotopes to provide targeted radiation therapy via alpha particles precisely to bone-forming tumors in addition to IFG1R or Her-2 expressing metastases. This review will detail experience using the alpha emitter radium-223 (223Ra, tradename Xofigo), that targets bone formation, in osteosarcoma, specifically related to patient selection, use of gemcitabine for radio-sensitization, and using denosumab to increasing the osteoblastic phenotype of these cancers. A case of an inoperable left upper lobe vertebral-paraspinal-mediastinal osteoblastic lesion treated successfully with 223Ra combined with gemcitabine is described. Because not all areas of osteosarcoma lesions are osteoblastic, but nearly all osteosarcoma cells overexpress IGF1R, and some subsets expressing Her-2, the anti-IGF1R antibody FPI-1434 linked to actinium-225 (225Ac) or the Her-2 antibody linked to thorium-227 (227Th) may become other means to provide targeted alpha particle therapy against osteosarcoma (NCT03746431 and NCT04147819).